2016
DOI: 10.3390/ijerph13080791
|View full text |Cite
|
Sign up to set email alerts
|

Sri Lanka Pilot Study to Examine Respiratory Health Effects and Personal PM2.5 Exposures from Cooking Indoors

Abstract: A pilot study of indoor air pollution produced by biomass cookstoves was conducted in 53 homes in Sri Lanka to assess respiratory conditions associated with stove type (“Anagi” or “Traditional”), kitchen characteristics (e.g., presence of a chimney in the home, indoor cooking area), and concentrations of personal and indoor particulate matter less than 2.5 micrometers in diameter (PM2.5). Each primary cook reported respiratory conditions for herself (cough, phlegm, wheeze, or asthma) and for children (wheeze o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 13 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…It is plausible because individuals with PTSD exhibit an altered phenotype of regulatory T cells (12) and furthermore, it has been suggested that asthma onset can be linked to family/personal disasters (13) which is the case in these shelter dwellers (loss of home and/or family member).There are also other adverse factors in shelter living. For example, cooking in the same room where the family lives may increase the exposure to particulate matters (PM 2.5 ) which can exacerbate asthma (14). Other triggers include use of detergent such as bleach (sodium hypochlorite), which is widely used in Syria (15) and amongst the shelter dwellers, exposure to SHS (16,17) and poverty (17,18) (the study participants had an average daily income of less than 2 USD/day).…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible because individuals with PTSD exhibit an altered phenotype of regulatory T cells (12) and furthermore, it has been suggested that asthma onset can be linked to family/personal disasters (13) which is the case in these shelter dwellers (loss of home and/or family member).There are also other adverse factors in shelter living. For example, cooking in the same room where the family lives may increase the exposure to particulate matters (PM 2.5 ) which can exacerbate asthma (14). Other triggers include use of detergent such as bleach (sodium hypochlorite), which is widely used in Syria (15) and amongst the shelter dwellers, exposure to SHS (16,17) and poverty (17,18) (the study participants had an average daily income of less than 2 USD/day).…”
Section: Discussionmentioning
confidence: 99%
“…In a study done to quantify PM2.5 exposure from cooking using biomass to adults and children in rural households in Sri Lanka, researchers used two PM monitors per household; one on the cook, and the other on the cook stove which was used to monitor the PM concentration in the vicinity of the kitchen and was also used as a surrogate to measure the exposure of the children [11].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It was found that there was a positive correlation in the number of respiratory health conditions the cook and their children had with respect to their PM exposure. Health effects included asthma, coughing, phlegm, and wheezing [11].…”
Section: Evaluation Of Health Effectsmentioning
confidence: 99%
See 2 more Smart Citations